The Neurobase of ambiguity loss aversion about decision making - Hu, Yiqin; Lu, Xinbo; Zheng, Wanjun; Wang, Luting; Yu, Ping (Frontiers in Psychology, 2023)
In our daily decision-making, there are two confusing problems: risk and ambiguity. Many psychological studies and neuroscience studies have shown that the prefrontal cortex (PFC) is an important neural mechanism for modulating the human brain in risk and ambiguity decision-making, especially the dorsolateral prefrontal cortex (DLPFC). We used transcranial direct current stimulation (tDCS) to reveal the causal relationship between the DLPFC and ambiguity decision-making. We design two experimental tasks involving ambiguity to gain and ambiguity to loss. The results of our study show that there is a significant effect on left DLPFC stimulation about ambiguity to loss, there is an insignificant effect on left DLPFC stimulation about ambiguity to gain, and there is an insignificant effect on right DLPFC stimulation about ambiguity to gain and ambiguity to loss. This result indicates that people are more sensitive to ambiguity loss than ambiguity gain. Further analysis found that the degree of participants’ attitudes toward ambiguity loss who received anodal simulation was lower than that who received sham stimulation across the left DLPFC, which means that the subjects had a strong ambiguity loss aversion after the participants received the anodal simulation of the left DLPFC.